EXAMINING THE ENFORCEMENT OF WILDLIFE CONSERVATION POLICIES IN INDIA: CHALLENGES AND OPPORTUNITIES IN TADOBA ANDHARI TIGER RESERVE, CHANDRAPUR DISTRICT - Sheikh, Niyaj Shabbir; Shaikh, Aejaz (ShodhKosh: Journal of Visual and Performing Arts, 2024)
India Wildlife Conservation Policies: A Step Towards Preserving Biodiversity and Protecting Endangered Species This paper examines the issues related to trap-and-release efficacy in a conservation context, using the Tadoba Andhari Tiger Reserve (TATR) as a case study to highlight some of the challenges and opportunities faced by conservation authorities in enforcing wildlife conservation policies. A combination of field observations, stakeholder interviews, and policy analysis by the researchers highlights major gaps in enforcement, including poaching threats, problems of human-wildlife interactions, and resource limitations. The role of local communities, technology-driven monitoring systems, and legal frameworks in reducing turtle bycatch is also discussed in the study. The findings show that although there aremany policies in place, lack of socio-economic conditions, low enforcement funding, and poor coordination among enforcement agencies are significant barriers that hinder the implementation of these policies. Nonetheless, the changing landscape, including eco-tourism, community engagement, and AI-based surveillance offer innovative solutions to improving conservation management. These findings offer practical guidance for policymakers seeking to enhance law enforcement strategies in order to promote sustainable conservation of wildlife in TATR and comparable protected areas.